Conservação pós-colheita de cultivares de feijão-vagem - Evangelista, Regina Marta [UNESP]; Cardoso, Antonio Ismael Inácio [UNESP]; Castro, Márcia Maria [UNESP]; Goldoni, Cristiano [UNESP] (Fundacao Educational de Ituverava, 2011)
There are great postharvest losses of snap-bean pods, however there are not studies comparing Brazilian cultivars for postharvest conservation and about techniques that provides lesser losses. The objective of this work was to evaluate the postharvest quality of four snap-bean cultivars (Preferido, Favorito, Itatiba and Teresópolis) and to evaluate postharvest quality when fruits of cultivar Preferido were stored with and without cooling in over-wrapping expanded polystyrene trays with (modified atmosphere - MA) and without PVC. In first experiment, treatments were pods of four cultivars stored at ambient temperature (29-32oC). In second experiment, pods of cultivar Preferido were divided in four treatments: control with ambient temperature (20- 25oC), control with cooling (7  1oC), MA with ambient temperature and MA with cooling. In both experiments, experimental design was randomized blocks, with five replicates and it was evaluated mass loss, change in the characteristic coloration, presence of fungi and general appearance of fruits each three days, until sixth day in first and until 12th day in second experiment. It was verified that cultivar Preferido presented the best results, maintaining its color and general appearance for six days, while the other cultivars maintained their appearance for only three days. It was verified, too, that fruits stored under cooling and with involvement of PVC film (modified atmosphere) showed the best results, maintaining its color and general appearance for 12 days, with the least mass loss.

Ocorrem grandes perdas após a colheita dos frutos de feijão-vagem, entretanto não existem estudos comparando as cultivares nacionais quanto à conservação pós-colheita, assim como de técnicas que visem reduzir estas perdas. O objetivo deste trabalho foi avaliar a qualidade pós-colheita e a "vida de prateleira" de quatro cultivares (Preferido, Favorito, Itatiba e Teresópolis) de feijão-vagem e também a qualidade póscolheita dos frutos da cultivar Preferido armazenados com e sem refrigeração e embalados em bandejas de poliestireno expandido e recobertos (atmosfera modificada - AM) ou não com policloreto de vinila (PVC). No primeiro experimento, os tratamentos foram as vagens recém-colhidas das quatro cultivares armazenadas em temperatura ambiente (29-32oC). No segundo experimento, os frutos do feijão-vagem ‘Preferido’ foram divididos em quatro tratamentos: testemunha ambiente (20-25oC), testemunha refrigerado (7  1oC), AM ambiente e AM refrigerado. Em ambos os experimentos, o delineamento experimental foi em blocos ao acaso, com cinco repetições e avaliou-se a perda de massa, mudança na coloração característica, presença de fungos e aparência geral dos frutos a cada três dias até o 6o dia no primeiro experimento e até o 12º dia no segundo. Constatou-se que a cultivar que apresentou os melhores resultados foi a Preferido, mantendo sua coloração e aparência geral por seis dias, ao contrário das demais que se mantiveram por apenas três dias. Também observou-se que os frutos armazenados sob refrigeração e com envolvimento de filme plástico (AM) apresentaram os melhores resultados, mantendo sua coloração e aparência geral por 12 dias, com a menor perda de massa.
Postharvest conservation of snap-bean cultivars
Keywords: Phaseolus vulgaris; Weight loss; Shelf life; Phaseolus vulgaris; Perda de massa; Vida de prateleira